2013
DOI: 10.1042/bj20130295
|View full text |Cite
|
Sign up to set email alerts
|

Extended interaction network of procollagen C-proteinase enhancer-1 in the extracellular matrix

Abstract: PCPE-1 (procollagen C-proteinase enhancer-1) is an extracellular matrix glycoprotein that can stimulate procollagen processing by procollagen C-proteinases such as BMP-1 (bone morphogenetic protein 1). PCPE-1 interacts with several proteins in addition to procollagens and BMP-1, suggesting that it could be involved in biological processes other than collagen maturation. We thus searched for additional partners of PCPE-1 in the extracellular matrix, which could provide new insights into its biological roles. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…Seventeen additional binding partners of PCPE-1, including laminin 111, collagen VI, thrombospondin 1, collagen IV and endostatin (a fragment of collagen XVIII) were identified recently by SPR (surface plasmon resonance) imaging (Salza et al, 2014). Surprisingly, neither recombinant syndecans-1, -2 or -4 nor fibronectin bound to PCPE-1 in the SPR binding assays.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Seventeen additional binding partners of PCPE-1, including laminin 111, collagen VI, thrombospondin 1, collagen IV and endostatin (a fragment of collagen XVIII) were identified recently by SPR (surface plasmon resonance) imaging (Salza et al, 2014). Surprisingly, neither recombinant syndecans-1, -2 or -4 nor fibronectin bound to PCPE-1 in the SPR binding assays.…”
Section: Discussionmentioning
confidence: 94%
“…The NTR domain also interacts with BMP-1 (Beckhouche et al, 2010) and mediates PCPE-1 binding to ␤2-microglobulin (Morimoto et al, 2008). Additional interaction targets of PCPE-1 in the ECM include laminin 111, collagens VI and IV, thrombospondin-1 and endostatin (Salza et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, because of recent in vitro evidence that PCPE-1 can bind the anti-angiogenic factor endostatin, and can itself inhibit angiogenesis in an in vitro assay (Salza, et al, 2014), corneas of WT and Pcolce −/− mice were examined for degree of neovascularization 5 days post alkali burn. Interestingly, a striking difference in neovascularization following the alkali burn was found between Pcolce −/− and WT corneas, with a marked increase in intracorneal hemangiogenesis in Pcolce −/− cornea compared with WT, as detected by light microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in PCPE-1 expression levels in quiescent versus proliferating smooth muscle cells (Kanaki, et al, 2000), and the induced anchorage-independent growth of cultured fibroblasts in which the PCPE-1 gene has been disrupted (Masuda, et al, 1998), have also suggested a possible role for PCPE-1 in cell proliferation control. It was also recently reported that PCPE-1 can bind the anti-angiogenic factor endostatin and can itself inhibit angiogenesis in an in vitro assay (Salza, et al, 2014). In addition, PCPE-1 may be necessary for lumen formation in a model of in vitro angiogenesis, although the latter effect may be secondary to PCPE-1’s role in collagen biosynthesis and consequent effects on extracellular matrix (ECM) stiffness (Newman, et al, 2011).…”
Section: Introductionmentioning
confidence: 94%